Regulation of the fetal mouse ductus arteriosus is dependent on interaction of nitric oxide and COX enzymes in the ductal wall - Reese, Jeff (2008)
Nitric oxide (NO) and cyclooxygenase (COX)-derived prostaglandins are critical regulators of the fetal ductus arteriosus. To examine the interaction of these pathways within the ductus wall, the ductus arteriosus of term and preterm fetal mice was evaluated by pressurized myography. The isolated preterm ductus was more sensitive to NOS inhibition than at term. Sequential NOS and COX inhibition caused 36% constriction of the preterm ductus regardless of drug order. In contrast, constriction of the term ductus was dependent on the sequence of inhibition; NOS inhibition prior to COX inhibition produced greater constriction than when inhibitors were given in reverse order (36±6% versus 23±5%). Selective COX-1 or COX-2 inhibition prior to L-NAME induced the expected degree of constriction. However, NOS inhibition followed by selective COX-2 inhibition caused unexpected ductal dilation. These findings are consistent with NO-induced activation of COX in the ductus arteriosus wall and the production of a COX-2-derived constrictor prostanoid that contributes to the balance of vasoactive forces that maintain fetal ductus arteriosus tone.